Foaming with scco2 and Impregnation with Cinnamaldehyde of Pla Nanocomposites for Food Packaging - Guarda-Moraga, A; Romero-Figueroa, J; Galotto-Lopez, M; Rojas-Sepulveda, A; Torres-Mediano, A; Riveros-Faba, S; Villegas-Vallejos, C; Velasquez, E; Rivera-Fuentealba, P (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
Microcellular nanocomposite foams functionalized with cinnamaldehyde (Ci) were obtained through two-step supercritical foaming and impregnation processing. PLA nanocomposite foams with different C30B concentrations (1, 2, and 3 wt.%) were obtained by foaming with scCO2 at 25 MPa and 135◦C and impregnated with Ci at 12 MPa and 40◦C. The effect of the C30B content and Ci incorporation on the morphological, structural, thermal, and release properties of the developed foams were investigated. The incorporation of Ci was not influenced by C30B’s addition. The presence of C30B and Ci incorporation reduced the average pore diameter slightly and the crystallinity degree of the foams extensively. Simultaneously, the experimental and theoretical characterization of the Ci release from the PLA nanocomposite foams in EtOH 50% was analyzed. The mechanism of Ci release from the foams was defined as a quasi-Fickian diffusion process that could be successfully described using the Korsmeyer–Peppas model. The active PLA foams presented a higher potential of migration and faster release when compared with that reported in commonly used PLA films, showing that biopolymeric foams could be potentially used as active food packaging to improve the migration of active compounds with low migration potentials in order to improve their biological activity in foods. © 2022 by the authors. Licensee MDPI, Basel, Switzerland.